Adult idiopathic hypertrophic pyloric stenosis - a common presentation with an uncommon diagnosis - Syed Moin Hassan; Ateeq Mubarik; Salman Muddassir; Furqan Haq (Greater Baltimore Medical Center, 2018)
Background and Objectives: Adult Idiopathic hypertrophic pyloric stenosis (AIHPS) is a rare but well-defined entity in adults with only 200-300 cases reported so far in the literature.We describe a case of AIHPS and the relevant literature review. Methods and Results: The patient presented with acute onset upper abdominal pain associated with nausea, vomiting, foul-smelling black tarry stools, and anorexia. On the Esophagogastroduodenoscopy (EGD), pylorus demonstrated a unique "cervix sign." The patient had multiple endoscopic dilations with minimal relief. She then underwent a distal partial gastrectomy with a Billroth 1 gastroduodenostomy with considerable  improvement in her symptoms on follow up. Conclusion: Adult Idiopathic hypertrophic pyloric stenosis (AIHPS) is a rare disease which is also underreported due to a difficulty in diagnosis. The most common symptoms of AIHPS are postprandial nausea, vomiting, early satiety, and epigastric pain as seen in our patient. Endoscopy usually shows ?Cervix sign? a unique sign showing a fixed, markedly narrowed pylorus with a smooth border. Multiple treatments have been proposed for AIHPS, including endoscopic dilation, pyloromyotomy with or without pyloroplasty, gastrectomy with a Billroth 1 gastroduodenostomy. Currently, there is no evidence of one surgical technique being superior to another. Further research needs to be done on AIHPS before one technique can be standardized as the standard of care.